PHYSIOTHERAPEUTIC ASSESSMENT AND REHABILITATION STRATEGIES OF THE SEQUELAE OF SURGICAL REMOVAL IN A IV VENTRICULUM’S TUMOR: A CASE STUDY - João Pereira Martins, Sandro (Health and Society, 2024)
Introduction: Tumor surgeries in the IV ventricle are challenging and hairsplitting due to the risk of injury in adjacent structures, such as, the cerebellum and vestibular nucleus, which can cause movement disorders, affecting balance and gait, resulting in a decrease in functional capacity and quality of life. Objectives: Find the most effective assessment and rehabilitation process, taking into account a whole bio-psycho-social that is the patient of this case study. Methodology: Subjective and objective assessment were performed, as well as a treatment plan to the patient in question. Results: Good results were recorded on the Berg Scale and Timed Up & Go (Tug). Discussion: A lot of literature talks about isolated treatments to treat sequelae of surgical procedures close to the cerebellum, however in this case study it is demonstrated that, supported by the existing scientific evidence, with the aid of clinical reasoning and critical thinking, it is possible to adapt and execute a assessment and rehabilitation process for those patients, in a safe and effective way. Conclusion: Physiotherapy, namely therapeutic massage, re-education of the gait pattern, namely facilitating the semi-step with handling in the foot, ankle and knee, balance training inspired by the Berg Scale, functional training with the promotion of dynamic instability and aerobic training, result in good strategies to decrease postural instability, maximize functional capacity and minimize complications in this kind of surgeries.